O4 Baricitinib-induced changes in STAT-associated gene expression in systemic lupus erythematosus. (23rd March 2020) - Dörner, Thomas; Tanaka, Yoshiya; Petri, Michelle; Smolen, Josef S; Wallace, Daniel J; Dow, Ernst R; Fantini, Damiano; Higgs, Richard E; Rocha, Guilherme; Crowe, Brenda; Benschop, Robert J; Byers, Nicole L; et al.
Abstract : Background: Baricitinib, an oral selective Janus kinase (JAK)1 and 2 inhibitor, resulted in significant clinical improvements in patients with active systemic lupus erythematosus (SLE) receiving standard background therapy in the phase 2 study JAHH (NCT02708095 ). Baricitinib may impact key cytokines implicated in the pathogenesis of SLE through effects on the JAK/signal transducer and activator of transcription (STAT) signaling pathway. The impact of baricitinib on STAT-related gene expression and associations with clinical response in SLE were evaluated. Methods: 314 patients were randomized 1:1:1 to receive once-daily placebo, baricitinib 2-mg, or baricitinib 4-mg for 24 weeks in JAHH. Patients were ≥18 years of age, had a diagnosis of SLE, and had active disease involving skin or joints. RNA isolated from whole blood at baseline and weeks 2, 4, 12, and 24 was analyzed using Affymetrix HTA2.0 array. Results: Gene expression profiling demonstrated a statistically significant elevation of STAT1 and STAT2 gene expression at baseline in SLE patients. There was a significant association between the overexpression of STAT1 and STAT2 at baseline. Baricitinib 4-mg treatment resulted in modest reduction in STAT1, STAT2, and STAT4 expression, and a statistically significant reduction in multiple genes downstream of STAT1, STAT2, and STAT4 . The reduction in expression of STAT-associated genes with baricitinib treatment correlated with clinical improvement in SLE patients using SLEDAI-2K measurements (table 1 ). Conclusions: Baricitinib may partially mediate its effect in SLE through changes in STAT-related gene expression, with changes associated with clinical improvement in SLE. Acknowledgements: Funded by Eli Lilly and Company.